Comparing exercise modalities during caloric restriction: a systematic review and network meta-analysis on body composition - Xie, Yongchao; Gu, Yu; Li, Zhen; Zhang, Lei; Hei, Yang (Frontiers in Nutrition, 2025)
BackgroundIn recent years, caloric restriction (CR), intermittent fasting (IF), and the ketogenic diet (KD) have gained popularity as primary dietary interventions for improving body composition. While these approaches offer benefits, both IF and KD have been associated with various adverse effects. Although CR is generally devoid of significant side effects, it may lead to reductions in lean body mass. To mitigate this, CR combined with exercise (CR + EX) has become a preferred strategy for maintaining overall health. However, under CR conditions, the effects of exercise may differ from those observed with a normal diet. Most existing studies compare CR + EX with CR alone, exercise alone, or a control (CON) group. Although prior studies have examined caloric restriction with exercise, direct comparisons between specific exercise modalities in a caloric deficit remain unclear, necessitating a network meta-analysis approach. This study summarizes the literature on CR combined with exercise to identify which exercise regimen, when paired with CR, yields the most favorable outcomes. The findings will provide valuable recommendations for individuals seeking to maintain or improve body composition through CR + EX.MethodsA systematic review was conducted in accordance with the PRISMA guidelines, covering literature from the inception of databases up to September 2024. Searches were performed in PubMed, Web of Science, Embase, and the Cochrane Library. This study was registered in PROSPERO under the identifier: CRD42024588241. Only randomized controlled trials (RCTs) involving healthy populations were included. Articles were rigorously screened according to the PICOS strategy (methods) eligibility criteria, and the risk of bias was assessed using the Cochrane Risk of Bias Tool. A network meta-analysis was performed, and the intervention effects were ranked using the Surface Under the Cumulative Ranking (SUCRA) curve.ResultsThe network meta-analysis included 62 RCTs, encompassing 4,429 participants. The ranking of intervention effects is as follows: Weight reduction: high-intensity aerobic exercise (HA) > moderate-intensity aerobic exercise (MA) > low-intensity aerobic exercise (LA) > moderate-intensity mixed exercise (MM) > high-intensity mixed exercise (HM) > CR > low-intensity resistance exercise (LR) > moderate-intensity resistance exercise (MR) > high-intensity resistance exercise (HR) > Control group (CON), Compared to CON, the effect sizes for the other groups were as follows: HA: 7.94 (6.34, 9.55), MA: 7.78 (5.97, 9.58), LA: 7.10 (5.10, 9.10), MM: 6.65 (3.49, 9.81), HM: 7.47 (3.19, 11.75), CR: 7.10 (5.10, 9.10), LR: 5.45 (0.17, 10.72), MR: 5.62 (3.17, 8.06), HR: 6.00 (3.24, 8.76); BMI reduction: LA > MM > HA > MA > HR > CR > HM > MR > CON; Fat mass reduction: LA > HA > HM > MA > MR > LR > HR > CR > MM > CON, Compared to CON, the effect sizes for the other groups were as follows: LA: 2.70 (1.76, 3.65), MM: 3.35 (1.94, 4.75), HA: 2.90 (2.11, 3.70), MA: 2.96 (2.09, 3.84), HR: 2.56 (1.43, 3.69), CR: 2.47 (1.79, 3.15), HM: 1.73 (−0.34, 3.81), MR: 2.26 (1.08, 3.45); Body fat percentage reduction: HA > MM > LR > HR > MR > HM > MA > LA > CR > CON, Compared to CON, the effect sizes for the other groups were as follows: HA: 4.80 (3.50, 6.10), MM: 5.87 (3.22, 8.52), LR: 6.24 (1.05, 11.42), HR: 4.40 (1.93, 6.87), MR: 4.18 (2.21, 6.15), HM: 4.40 (0.80, 7.99), MA: 4.17 (2.70, 5.64), LA: 3.40 (1.44, 5.35), CR: 3.23 (2.08, 4.39); Lean body mass preservation: CON > MM > MR > LR > HR > MA > LA > HM > HA > CR, Compared to CON, the effect sizes of the other groups were as follows: MM: 0.14 (−2.91, 3.19), MR: 0.03 (−2.24, 2.29), LR: 0.36 (−4.15, 4.87), HR: −0.17 (−2.36, 2.02), MA: −0.40 (−2.22, 1.43), LA: −0.58 (−2.75, 1.59), HM: −0.81 (−4.27, 2.65), HA: −0.67 (−2.33, 0.98), CR: −1.66 (−3.12, −0.19). In summary, LR + CR, MA + CR and MR + CR are at an advantageous level in improving various indicators.ConclusionCombining moderate-and low-intensity resistance or aerobic exercise with caloric restriction optimizes fat loss while preserving lean body mass, making it a superior strategy for body composition improvement.Systematic review registrationThis study was registered in PROSPERO under the identifier: CRD42024588241.